1978
DOI: 10.1002/ana.410030209
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of a possible association between house dogs and multiple sclerosis

Abstract: The present study was undertaken because of the recent report of an association between familial multiple sclerosis (MS) and prior ownership of a small pet. Forty-five patients with sporadic MS were retrospectively compared with 45 closely matched controls and were found to have owned a significantly greater number of indoor dogs prior to the onset of MS. Importantly, the MS patients had also had more exposure to neurologically ill dogs in the five years before the onset of symptoms. These new data further sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
2

Year Published

1978
1978
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 6 publications
1
20
2
Order By: Relevance
“…Our results give no clear support to earlier findings (12,(27)(28)(29)(30)34) that animal contact may be a risk factor for developing multiple sclerosis. In the pathogenetic discussion of multiple sclerosis, several infectious agents have been suggested as directly or indirectly inducing or precipitating the development of multiple sclerosis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Etiologic Aspectscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results give no clear support to earlier findings (12,(27)(28)(29)(30)34) that animal contact may be a risk factor for developing multiple sclerosis. In the pathogenetic discussion of multiple sclerosis, several infectious agents have been suggested as directly or indirectly inducing or precipitating the development of multiple sclerosis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Etiologic Aspectscontrasting
confidence: 99%
“…Many studies have shown that animal contacts could mean a higher risk (27)(28)(29)(30), but in a later review of the etiologic importance of such contacts the results have been ambiguous, with some of the nonp ositive studies bearin g more weight (3 1). Hence the pathogenesis is likely to be complex -both genetic and environmental factors may be invol ved and interact (32) .…”
mentioning
confidence: 99%
“…It is of interest that sibs ofMS patients who do not have clinical signs ofMS also tend to have higher titers of measles antibody than do controls [17], but either genetic factors or common exposure to an etiologic agent could account for the familial aggregation of the measles titer elevation. CDV titers are allegedly increased in MS according to one group [21], but at least one attempt to confirm this result in a small series failed [30]. The higher CDV titer would fit with those reports which have described a higher exposure to small household dogs among MS patients than among controls.…”
supporting
confidence: 58%
“…The observations suggesting an association between occurrence of MS in the Faroes and occupation of these islands by British troops in World War II is relevant to the question of dog exposure and MS [21]. According to one report, dogs on the Faroes were not inoculated [19] against distemper, and an epizootic of canine distemper occurred in the Faroes after the British occupation because the British troops brought dogs with them.…”
mentioning
confidence: 99%
“…We are not certain of the origin of the previously demonstrated increases in CK-MB and CK-MM activity in some patients with cerebrovascular accidents as described in the work of Dub0 et al [2]. It is known from previous experiments that release of CK-MB from the heart m a y occur with stimulation of certain portions of the brain.…”
mentioning
confidence: 77%